PROSPECTS FOR THE STRATEGIC DEVELOPMENT OF CLUSTERS AND THEIR ECONOMIC EFFICIENCY - Rakhimov, Odil Berdiyevich (THE INNOVATION ECONOMY, 2026)
The article examines the process of regional development through clustering and emphasizes how the future development of clusters contributes to the formation of modern economic and social infrastructures in the regions. An econometric model of the production activities of the “Sulton Tex Groop” cotton-textile cluster has been developed and analyzed. In addition, the study highlights the main factors determining the economic and social efficiency of modern clusters.